2000
DOI: 10.1007/s150100050077
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Fulminant Mycoplasma pneumoniae Pneumonia within 4 Months

Abstract: We report the clinical course and diagnostic findings in two patients with life-threatening Mycoplasma pneumoniae (MP) pneumonia who were treated in the same hospital in the course of only 4 months. The patients were previously healthy adults, aged 31 and 37 years, respectively. In both of them severe complications occurred which coincided with the acute MP respiratory infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…There are several descriptions of severe cases of My coplasma pneumoniae pneumonia with and without associated multi-organ failure [15][16][17][18][19]. Clinically severe cases of M. pneumoniae pneumonia published before 1995 have been reviewed by Chan and Welsh [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are several descriptions of severe cases of My coplasma pneumoniae pneumonia with and without associated multi-organ failure [15][16][17][18][19]. Clinically severe cases of M. pneumoniae pneumonia published before 1995 have been reviewed by Chan and Welsh [13].…”
Section: Discussionmentioning
confidence: 99%
“…Layh-Schmitt et al (6,(39)(40)(41)(42)(43)(44)(45)66) showed that MGPC gene products (accessory proteins B and C) are essential for M. pneumoniae cytadherence. MGPC gene products are found in close proximity to ADP1 as well as to other cytadherencerelated molecules, such as HMW1, HMW3, p65, and p30 in M. pneumoniae (42,45,66).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 10% of cases are clinically apparent and fewer than 5% of those cases requiring hospitalization. [3][4][5] Of those requiring hospitalization, 10% will require admission to an intensive care unit (ICU) with mechanical ventilation as a result of Acute Respiratory Distress Syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%
“…The literature presents cases where a previously healthy subject, between the ages of 18 and 37, progressed to ARDS and the associated severe complications. [4][5][6][7][8] Many of these cases presented for medical treatment after up to 10 days of non-specific symptoms such as fatigue, myalgia, and low-to high-grade fever. The majority of these cases received appropriate medical care, including antibiotic therapy, at time of presentation.…”
Section: Introductionmentioning
confidence: 99%